PCB169 exposure aggravated the development of non-alcoholic fatty liver in high-fat diet-induced male C57BL/6 mice - Wei, Yunli; Zhou, Guangxian; Lv, Guangzhou; Wei, Wan; Shera, Lunguelizabeth; Lin, Hongying; Chen, Jinjun; Kang, Danju (Frontiers in Nutrition, 2024)
Polychlorinated biphenyls (PCBs) are lipophilic environmental toxicants. Epidemiological studies have established a link between PCBs and both metabolic syndrome and nonalcoholic fatty liver disease (NAFLD). Multiple studies have reported that exposure to both PCB156 and PCB126 among the 12 dioxin-like PCBs leads to the development of NAFLD. However, studies to elucidate whether PCB169 induces the development of NAFLD by constructing in vivo models have not been reported. Therefore, we evaluated the effects of exposure to PCB169 (5 mg/kg-bw) on hepatic lipid metabolism in C57BL/6 mice from control diet and high-fat diet cohorts. The results showed that PCB169 exposure resulted in both weight loss and a decrease in intra-abdominal fat mass, but significantly increased hepatic lipid levels and decreased fat mass in mice in the control diet group and exacerbated NAFLD in the high-fat diet group. Through transcriptomics studies, it was found that PCB169 exposure induced significant up-regulation of Pparγ, Fasn, and Aacs genes involved in hepatic lipogenesis, as well as remarkable up-regulation of Hmgcr, Lss, and Sqle genes involved in cholesterol synthesis. Additionally, there was notable down-regulation of Pparα and Cpt1 genes involved in lipid β-oxidation, leading to abnormal lipid accumulation in the liver. In addition, we found that PCB169 exposure significantly activated the Arachidonic acid metabolism, PPAR signaling pathway, Metabolism of xenobiotics by cytochrome P450, and Retinol metabolism pathways, and so on. Our study suggests that PCB169 can modify gene expression related to lipid metabolism, augument lipid accumulation in the liver, and further contribute to the development of NAFLD, thereby revealing the detrimental effects associated with PCB exposure on animal growth and metabolism.